Simultaneous RNAi Knockdown of Three FMRFamide-Like Peptide Genes, Mi-flp1, Mi-flp12, and Mi-flp18 Provides Resistance to Root-Knot Nematode, Meloidogyne incognita - Banakar, Prakash; Hada, Alkesh; Papolu, Pradeep K.; Rao, Uma (Frontiers in Microbiology, 2020)
Root-knot nematode, Meloidogyne incognita, is a devastating sedentary endoparasite that causes considerable damage to agricultural crops worldwide. Modern approaches targeting the physiological processes have confirmed the potential of FMRFamide like peptide (FLPs) family of neuromotor genes for nematode management. Here, we assessed the knock down effect of Mi-flp1, Mi-flp12 and Mi-flp18 of M. incognita and their combinatorial fusion cassette on infection and reproduction. Comparative developmental profiling revealed higher expression of all three FLPs in the infective 2nd stage juveniles (J2s). Further, Mi-flp1 expression in J2s could be localized in the ventral pharyngeal nerves near to metacarpal bulb of the central nervous system. In vitro RNAi silencing of three FLPs and their fusion cassette in M. incognita J2s showed that combinatorial silencing is the most effective and affected nematode host recognition followed by reduced penetration ability and subsequent infection into tomato and adzuki bean roots. Northern blot analysis of J2s soaked in fusion dsRNA revealed the presence of siRNA of all three target FLPs establishing successful processing of fusion gene dsRNA in the J2s. Further, evaluation of the fusion gene cassette is done through host-delivered RNAi in tobacco. Transgenic plants with fusion gene RNA-expressing vector were generated in which transgene integration was confirmed by PCR, qRT-PCR, and Southern blot analysis. Transcript accumulation of three FLPs constituting the fusion gene was reduced in the M. incognita females collected from the transgenic plants that provided additional evidence for successful gene silencing. Evaluation of positive T1 transgenic lines against M. incognita brought down the disease burden as indicated by various disease parameters that ultimately reduced the nematode multiplication factor (MF) by 85% compared to the wild-type plants. The study establishes the possibility of simultaneous silencing of more than one FLPs gene for effective management of M. incognita.